Great Lakes Basin Heat Waves: An Analysis of Their Increasing Probability of Occurrence Under Global Warming - Xie, Fengyi; Erler, Andre R.; Chandan, Deepak; Peltier, W. Richard (Frontiers in Water, 2021)
Extreme heat events in the Great Lakes Basin (GLB) region of eastern North America are expected to increase in concert with greenhouse gas (GHG) induced global warming. The extent of this regional increase is also influenced by the direct effects of the Great Lakes themselves. This paper describes results from an ensemble of dynamically downscaled global warming projection using the Weather Research and Forecast (WRF) regional climate model coupled to the Freshwater Lake (FLake) model over the Great Lakes region. In our downscaling pipeline, we explore two sets of WRF physics configurations, with the initial and boundary conditions provided by four different fully coupled Global Climate Models (GCMs). Three time periods are investigated, namely an instrumental period (1979–1989) that is employed for validation, and a mid-century (2050–2060) and an end-century (2085–2100) periods that are used to understand the future impacts of global warming. Results from the instrumental period are characterized by large variations in climate states between the ensemble members, which is attributed to differences in both GCM forcing and WRF physics configuration. Results for the future periods, however, are such that the regional model results have good agreement with GCM results insofar as the rise of average temperature with GHG is concerned. Analysis of extreme heat events suggests that the occurrence rate of such events increase steadily with rising temperature, and that the Great Lakes exert strong lake effect influence on extreme heat events in this region.